The Efficacy of Conbercept in Polypoidal Choroidal Vasculopathy: A Systematic Review. (13th August 2020) - Wang, Yimin; Shen, Mengxi; Cheng, Jinwei; Sun, Xiaodong; Kaiser, Peter K.
Abstract : Topic . The aim of this study is to evaluate the efficacy of conbercept in PCV, which will optimize the management for PCV patients. Clinical Relevance . The use of antivascular endothelial growth factor (VEGF) therapy in polypoidal choroidal vasculopathy (PCV), a subtype of neovascular age-related macular degeneration (nAMD), has been well established in randomized clinical trials. This meta-analysis has evaluated the efficacy of a novel anti-VEGF agent, conbercept, in the management of PCV using ranibizumab and aflibercept as the reference agents. Methods . Thirty studies with 1308 eyes were identified and included in this study. The primary outcome measures were best-corrected visual acuity (BCVA), and secondary outcomes were optical coherence tomography characteristics and polyp regression rates. The pooled results were calculated by the random-effect or fixed-effect model according to the heterogeneity of the data. Results . Despite a large standard deviation in means (SMD) improvement for BCVA and central retinal thickness (CRT) in the conbercept group, there was no statistically significant difference in the other outcomes compared to ranibizumab and aflibercept. However, there was a greater polyp regression rate in the conbercept group at 12 months. Conclusions . This systematic review indicates that conbercept may achieve similar BCVA and CRT improvements as ranibizumab and aflibercept, with a superior rate of polyp regression at 12 months.